IMPLEMENTATION OF PJBL WITH INTERACTIVE MEDIA FOR TEACHING INSTRUCTION TEXTS TO GRADE IV BAKALREJO 2 STUDENTS - Muhammad Wahyu Hidayat; Evi Chamalah; Rida Fironika Kusumadewi (Al-Irsyad: Journal of Education Science, 2025)
This study examines the learning challenges in Grade IV of Bakalrejo 2 Elementary School, such as low student understanding of instructional texts, minimal involvement in class, and less communicative teaching methods. Although the Project-Based Learning (PjBL) model has been proven to improve learning outcomes, its specific application in instructional text learning has rarely been studied. Most previous studies have only focused on general literacy or understanding of narrative texts, not instructional texts that require spatial reasoning, such as reading floor plans. This study presents a novelty by combining the PjBL model and interactive visual media such as floor plans, to improve students' understanding of instructional texts. This study uses a qualitative descriptive approach and includes classroom observations, LKPD analysis, and student project evaluations. The main focus of the study is: (1) students' ability to understand texts, (2) stages of PjBL implementation, and (3) utilization of interactive media as an aid. The results of the study indicate that the integration of PjBL with visual media can improve students' understanding and involvement in learning. This approach makes a positive contribution to improving the quality of Indonesian language learning at the elementary school level.